Distribución geográfica de Scincella incerta (Squamata: Scincidae) en el estado de Chiapas, México - Valdenegro-Brito, Antonio Esaú; Pavón-Vázquez, Carlos Joaquín; Luna-Reyes, Roberto; García-Vázquez, Uri Omar (Instituto de Ecología, A.C., 2018)
New records of Sincella incerta in Chiapas State are presented and its presence confirmed in the central region of the State. One of the records from the southeastern coastal foothills fills a gap in the distribution of the species between previous records from Chiapas and Guatemala.